138 Phase 1 dose-escalation study of STRO-002, an anti-folate receptor alpha (FRα) antibody drug conjugate (ADC), in patients with advanced platinum-resistant/refractory epithelial ovarian cancer (OC). (13th November 2020) - Naumann, R; Braiteh, F; Diaz, J; Hamilton, E; Diab, S; Schilder, R; Moroney, J; Martin, L; Uyar, D; O'Malley, D; Penson, R; DiLea, C; et al.
Abstract : Introduction: STRO-002 is a novel FRα-targeting ADC that delivers SC209, a potent tubulin-targeting hemiasterlin cytotoxin-warhead. Methods: All patients in the ongoing dose escalation study (NCT03748186 ) had platinum resistant/refractory OC without selection for FRα expression. STRO-002 is given IV on Day 1 of each 21-day cycle. Results: 38 patients have been dosed at 9 dose levels (0.5 to 6.4 mg/kg). Median number of cycles given is 3 (1–18). Median age is 61 (48–79). Median prior therapies - 5 (2–10). Clinically active doses (≥ 2.9 mg/kg) have been administered to 33 patients. 21/33 (64%) remain on treatment. Partial response was seen in 5 of 29 evaluable patients (17%) with 2 confirmed on second scan. 9 pts have confirmed SD for a clinical benefit rate of 48% (14/29). CA125 reduction of >50% was seen in 14/22 (64%) evaluable patients per GCIG. Clinical activity appears to be durable with 36% and 24% on study >16 and >24 weeks, respectively. 88% of AEs are grade 1 or 2. Grade 3–4 neutropenia, an expected and reversible effect of STRO-002 occurred in 15/38 (39%). DLTs reported – grade 3 neuropathy (6.0 mg/kg) and grade 3 bone pain (6.4 mg/kg). Conclusions: STRO-002 is a novel FRα-targeting ADC with a promising emerging safety and efficacy profile and preliminary clinical benefit/disease control rate of 48% in patients with relapsed/refractory OC treated at ≥ 2.9 mg/kg. No ocular toxicity signals have been observed, suggesting potential differentiation from other FRα-targeting investigational therapies. Expansion cohorts in less heavily pre-treated patients are planned for 4Q20.